1976
DOI: 10.1103/physrevd.14.1217
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of radial scaling in single-particle inclusive reactions

Abstract: An analysis of an extensive sample of the world's data has been performed to test the hypothesis of radial scaling. We have studied the inclusive reactions p + p --+ (~* %~ or K * or p or 9) +anything to determine the behavior of the invariant cross section as a function of p,, x, = E*/E*,,,, the radial scaling variable, and s.The data cover a range in p, from 0.25 to -6.0 GeV/c and a range in d s from 3.0 to 63 GeV. For small x, and all available p, the single-particle inclusive cross sections for the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…A reasonable fit to data has been obtained by following the empirical observation that the longitudinal momentum distributions of the leading nucleon in pp collisions is flat [24], which translates into a linear rise of the inclusive invariant cross section as a function of x R . The transverse momentum distribution is also affected by the leading particle effect, resulting in an enhanced leading particle production in the forward direction (see for example [19,23]). In the proton fit, this is empirically accounted for by the term (…”
Section: The Parameterization Of Inclusive Invariant Cross Sectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A reasonable fit to data has been obtained by following the empirical observation that the longitudinal momentum distributions of the leading nucleon in pp collisions is flat [24], which translates into a linear rise of the inclusive invariant cross section as a function of x R . The transverse momentum distribution is also affected by the leading particle effect, resulting in an enhanced leading particle production in the forward direction (see for example [19,23]). In the proton fit, this is empirically accounted for by the term (…”
Section: The Parameterization Of Inclusive Invariant Cross Sectionsmentioning
confidence: 99%
“…An alternative scaling variable x R = E * /E * max , defined as the ratio of the energy of the detected particle in the centre-of-momentum frame and the maximum energy kinematically available to the detected particle, was suggested by Yen [18] and Taylor et al [19] and shown to greatly extend the range of validity of scaling at subasymptotic energies. As discussed in section 4.2, in the comparison of NA56/SPY and NA20 data to pBe data collected at lower energies, we have not observed an improved scale invariance when x R is used.…”
Section: The Parameterization Of Inclusive Invariant Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The x R = E ′ /E ′ max , defined as the ratio of the energy of the detected particle in the center of mass frame and the maximum energy kinematically available extends the range of validity of scaling [69,70]. For our purposes even the variable x lab = p L /p 0 where p L is the longitudinal component of the momentum of the secondary and p 0 is the momentum of the primary beam is sufficiently good scaling variable.…”
mentioning
confidence: 99%
“…It allows particle production to be quantitatively described in the most simple way possible and allows data collected with different initial proton beam momenta to be compared. Under two conditions, the produced particle is ultrarelativisic, E ≫ m, and it's divergence is very small, p z ≫ p T , the Feynman scaling variable can be expressed as x F ≃ p z /p 0 , where p 0 is the momentum of the incident particle [61,62].…”
Section: Monte Carlo Simulation Of the Beamlinementioning
confidence: 99%